A DESCRIPTIVE STUDY OF THE SWEARINGS FOUND IN CRAWL MOVIE BY ALEXANDRE AJA - Iin Hasanah; Wiwin Indiarti; Yuli Sugianto (LUNAR, 2022)
This research was a descriptive qualitative research. Aim at describers types and motives of swearing uttered by Dave and Halley in Crawl Movie by Alexander Aja. This research focused in analyzing words which contain swearing that are used by Haley Keller and Dave in Crawl Movie by Alexander Aja. The scope of this research is Sociolinguistics field that has function to know the relationship between language and society. This research only focuses in analyzing the types of swearing and the motive of using swearing.. The researcher used documentation method to collect the data. In this research, the researcher applied three steps of data analysis made by Miles and Huberman theory, those three steos are data reduction, data display and conclusion drawing/verification. The researcher found that there are 3 types of swearing that is used in Crawl Movie. Those are expletive, abusive, and auxiliary. The expletive is the most swearing uttered by the characters in Crawl Movie. They appeared 22 times. It is followed by the abusive which are uttered 5 times and auxiliary are uttered 5 times. Therefore, there are 3 kinds of swearing motives. They are psychological, social and linguistic motives. Psychological is the most motive used in the movie. Swearing with psychological motive occurred 24 times. Meanwhile, linguistic motive occurred 5 times. Then, social motive only occurred 3 times.